Epidemiologia das infecções por nematódeos gatrintestinais em ovinos criados em Botucatu - Wilmsen, Maurício Orlando [UNESP] (2014)
The epidemiology of gastrointestinal nematode infections was evaluated in sheep raised in Botucatu – SP. Every month, from April 2008 until March 2011, two tracer lambs were exposed to natural infection with gastrointestinal nematodes for 28 consecutive days, while grazing together with a sheep flock. Haemonchus contortus presented the highest infection intensities with 100% prevalence. There was no significant influence of the seasons in H. contortus infection intensity. Trichostrongylus colubriformis also presented 100% prevalence with the lowest infection intensity during the summer months. In the case of T. colubriformis, there was significant correlation coefficient between worm counts x precipitation (r = -0.32; P < 0.05). Other three nematodes species were found in tracer lambs, however, in small numbers. Their prevalence and mean intensity of infection (in parenthesis) were the following: Oesophagostomum columbianum 28% (25.2), Cooperia curticei 7% (4.5) and Trichuris spp. 2% (1). In conclusion, the environmental conditions of the area were very favourable for H. contortus and T. colubriformis transmission all year round. These explain in part the failure of private and governmental programs to promote the sheep breeding activity in São Paulo State due to high sheep mortality rates and low productivity caused by gastrointestinal nematode infections